2012
DOI: 10.1063/1.3675446
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh dielectric constant of thin films obtained by electrostatic force microscopy and artificial neural networks

Abstract: Copyright 2012 American Institute of Physics. This article may be downloaded for personal use only. Any other use requires prior permission of the author and the American Institute of Physics.A detailed analysis of the electrostatic interaction between an electrostatic force microscope tip and a thin film is presented. By using artificial neural networks, an equivalent semiinfinite sample has been described as an excellent approximation to characterize the whole thin film sample. A useful analytical expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…[34] The most notable result here is that only thin films with ultrahigh dielectric constants (at least ten times larger than typical values) can be detected when the thin film thickness is nanometric. Moreover, thin films with ultrahigh dielectric constants can be easily distinguished, which is something unexpected since they converge to the metallic case when the sample is macroscopic.…”
Section: Ai In Scanning Probe Microscopymentioning
confidence: 70%
“…[34] The most notable result here is that only thin films with ultrahigh dielectric constants (at least ten times larger than typical values) can be detected when the thin film thickness is nanometric. Moreover, thin films with ultrahigh dielectric constants can be easily distinguished, which is something unexpected since they converge to the metallic case when the sample is macroscopic.…”
Section: Ai In Scanning Probe Microscopymentioning
confidence: 70%
“…The error found in this case, R[F]=3.15%, is the average value for the whole set of curves analyzed . We can establish here that the sample composed by two layers (thin film and substrate) can be replaced by a single dielectric layer with a dielectric constant Ceff, in the same way that was previously reported [19] for thin films over semi infinite substrates. However, we have found that the ceer values are different when a metallic plate is included in the system.…”
Section: Re Sultsmentioning
confidence: 89%
“…We also show the Ceff values that would be obtained by the ANN, following the analytical approximation developed in [19 ] (called ANN values in the figure). The main difference between those values is that the ones from [19] are obtained by a semiinfinte substrate below the thin film and the values calculated here include the influence of the metallic plate. As we can see, ANN values for different C] are almost the same in the four figures (i.e.…”
Section: Re Sultsmentioning
confidence: 99%
“…A potential difference U is applied on this capacitor. As the finite element method is known for its gluttony of memory and computing time, we restrict to studying structure through simulations of the unit cells shown in Figure 2.The material is exposed to a static electric field that is generated by a voltage between the opposite faces of the unit cell [2,6,[17][18][19]. The potential distribution is determined from the Laplace equation inside the unit cell [18][19].…”
Section: Physical Model and Finite Element Methodsmentioning
confidence: 99%